2015
DOI: 10.1007/s11906-015-0587-4
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Carotid Sinus Stimulation: Chances and Challenges in the Management of Treatment Resistant Arterial Hypertension

Abstract: Treatment resistant arterial hypertension is associated with excess cardiovascular morbidity and mortality. Electrical carotid sinus stimulators engaging baroreflex afferent activity have been developed for such patients. Indeed, baroreflex mechanisms contribute to long-term blood pressure control by governing efferent sympathetic and parasympathetic activity. The first-generation carotid sinus stimulator applying bilateral bipolar stimulation reduced blood pressure in a controlled clinical trial but neverthel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…The first-generation system used in the present study consisting of tripolar electrodes implanted bilaterally (Rheos system) is no longer available for either experimental or clinical investigation. As cogently discussed, 4 patients currently receive only unilateral carotid sinus implants with an electrode of a different design (Barostim Neo). While recent findings using this second-generation system in patients with RHT do show blood pressure reductions with minimal or no side effects, 4648 unlike its predecessor, the Barostim Neo electrode system has only been tested in uncontrolled clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first-generation system used in the present study consisting of tripolar electrodes implanted bilaterally (Rheos system) is no longer available for either experimental or clinical investigation. As cogently discussed, 4 patients currently receive only unilateral carotid sinus implants with an electrode of a different design (Barostim Neo). While recent findings using this second-generation system in patients with RHT do show blood pressure reductions with minimal or no side effects, 4648 unlike its predecessor, the Barostim Neo electrode system has only been tested in uncontrolled clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…While recent findings using this second-generation system in patients with RHT do show blood pressure reductions with minimal or no side effects, 4648 unlike its predecessor, the Barostim Neo electrode system has only been tested in uncontrolled clinical trials. 45 Notably, a recent acute study in patients employing 2 min periods of unilateral carotid sinus activation suggested that the new electrode design may diminish efficacy and tolerability. 49 However, this has not been our experience when using the Barostim Neo system during chronic bilateral carotid sinus activation in canines.…”
Section: Discussionmentioning
confidence: 99%
“…While there is virtually no information from prospective studies or current clinical trials relating to the antihypertensive effects of carotid body ablation in humans, recent clinical trials have clearly shown that baroreflex activation reduces arterial pressure in many but not all patients with resistant hypertension. 1317 The reasons for this variability are not well understood, but as both baroreflex activation and carotid body denervation lower arterial pressure by inhibiting sympathetic activity, the variable degree of sympathetic activation in this heterogeneous population may be a key determinant of the antihypertensive response. 19 Obesity-induced hypertension is mediated by activation of the sympathetic nervous system and obesity is common in patients with resistant hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Using this technology, significant antihypertensive responses have been reported in both experimental animals and in patients with resistant hypertension. 1317 …”
Section: Introductionmentioning
confidence: 99%
“…Её роль в повышении давления, в вазоконстрикции и задержке жидкости, в развитии тахикардии несомненна и известна давно. Современ-ные исследования так или иначе пытаются влиять на симпатическую активность фармакологически или физически: воздействуя на каротидный синус или денервируя почки [1,2]. Однако инвазивные или малоинвазивные вмешательства не всегда возможны и не всегда показаны.…”
unclassified